(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Scheduled caste and scheduled tribes are the most backward sections of Indian society in terms of Educational development. Education is the key to development of any community. It can broaden the world view of the people, equipping them to meet the present day challenges. It can also build up inner strength of the people. The role of education as an investment in human resources’ has been increasingly recognized all over the underdeveloped and developed countries. Education has special significance for the weaker section of society, which are facing a new situation in the development process to adjust themselves property to the changing circumstances. For them education is an input not only for their economic development, but for promoting in them self-confidence and inner strength to face the new challenges.